Characteristic of the Three Pig Keeping Systems on Performance of Small-Scale Pig Farmers at Manokwari, West Papua - D.A. Iyai; S.Y. Randa (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
Pig keeping systems consisted of extensive, semi-intensive and intensive systems were studied to seek its performances on pigs and small-scale pig farmers. From six districts and 15 villages, 50 respondents were chosen. Characteristic of farmers and pig keeping systems were studied. Animal number used were 355 tails for measuring pig variables consisted of body weight, reproduction and herd size. Labor and experience were varied among the three pig keeping systems (P<0.05). Animal herd, farrowing rate, suckling piglet number and its body weight, weaned body weight and adult body weight were differ significantly (P<0.05) particularly on semi-penned pig keeping. Pig production efficiency and pig production productivity used as qualitative characteristic were not drawing animal efficiency and producivity.